Legal Sanction of Kesepekang in Balinese Customary System (In Perspective: Empiricism Theory of David Hume) - I Ketut Seregig (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
Legal sanction of Kesepekang is a moral sanction that has been a habit in Balinese custom society and has been done from generation to generation, both the one in Bali and outside Balinese custom society. The implementation of Kesepekang sanction currently is considered by the intellectuals of Balinese custom society as a behavior that violates social values in society. In its development, legal sanction of Kesepekang has been politicized as a factor causing the occurrence of custom society disharmony, both the one in Bali and outside Bali. This society resistance has weakened the function of Balinese customary law sourced from one of Hinduism belief which is “believing the presence of karmaphala (result from behavior) law.” The issue occurring in Balinese custom society, especially the one in the Province of Lampung, is “whether the legal sanction of kesepekang is still relevant if it is applied in Balinese traditional system.”  Based on the observation result, the term of Kesepekang is the attitude of “silence” that is done by the other members of customers who do not obey the customary regulations in their groups. Certain groups consider that the legal sanction of Kesepekang has violated human nature as social beings. To prove this argument, a study entitled: Legal Sanction of Kesepekang in Balinese Customary System–(In Perspective: Empiricism Theory of David Hume) is conducted. The result of the study can be concluded that the legal principles in Kesepekang sanction are the law of causation (causality), which each action certainly affects “when doing good, the result will be good – when doing bad, the result will be bad.” In the perspective of David Hume’s Empiricism theory, Kesepekang sanction is a sensory experience that occurs in custom society. Experience, according to David Hume, is the only source of knowledge, so the act of “silence” done by the member of custom as the effort in giving punishment to the member of customer who does not obey is a reality received by sense as an experience. Keywords: Kesepekang Legal Sanction, Empiricism Truth Theory